2015
DOI: 10.1016/j.jand.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Weighing Every Day Matters: Daily Weighing Improves Weight Loss and Adoption of Weight Control Behaviors

Abstract: Background Daily weighing is emerging as the recommended self-weighing frequency for weight loss. This is likely because it improves adoption of weight control behaviors. Objective Examine whether weighing everyday is associated with greater adoption of weight control behaviors compared to less frequent weighing. Design Longitudinal analysis of a previously conducted 6-month randomized-controlled trial. Participants/setting Overweight men and women in Chapel Hill, NC in the Intervention arm (N=47). Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 35 publications
8
84
0
4
Order By: Relevance
“…Behavioral approaches that utilize self-monitoring are a basic component of weight management programs with regular monitoring of body weight associated with successful weight loss and prevention of weight regain after weight loss [26,27]. Attributes of successful self-monitoring program include selection of measurements that are simple, are easy to perform, are not costly, use commonly available equipment, are performed accurately and privately, yield meaningful information for the individual, and may be shared with a health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral approaches that utilize self-monitoring are a basic component of weight management programs with regular monitoring of body weight associated with successful weight loss and prevention of weight regain after weight loss [26,27]. Attributes of successful self-monitoring program include selection of measurements that are simple, are easy to perform, are not costly, use commonly available equipment, are performed accurately and privately, yield meaningful information for the individual, and may be shared with a health care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Weighing regularly at established times provides participants with feedback about their weight loss progress and provides an opportunity to reflect on behaviors that have led to weight changes [72]. Structured weighing is also a hallmark of a CBT approach to EDs and is encouraged to replace either too-frequent weighing or avoidance of weighing that can perpetuate disordered eating thoughts and behaviors [70].…”
Section: Fbt Treatment Componentsmentioning
confidence: 99%
“…[17] Completion of the IVR calls was significantly correlated with weight loss. Two other studies also found that more daily weighing was associated with greater weight loss during a six-month intervention [19] or during the first six months of an 18-month intervention. [20] In the CITY study, among all features of the smartphone app, a greater percentage of days participants weighed self was independently correlated with greater weight loss in both groups.…”
Section: Discussionmentioning
confidence: 89%
“…Other research has also shown that weight loss was associated with greater engagement with participant self-weighing. [16,19,21, 22] A 6-month intervention showed that participants in the intervention group self-weighed more days/week (6.1 +/-1.1) than controls (1.1+/-1.5) and these participants lost significantly more weight than controls (-6.55% vs -0.35%).…”
Section: Discussionmentioning
confidence: 99%